Association between preoperative serum insulin levels and lymph node metastasis in endometrial cancer—a prospective cohort study. (13th March 2018) - Mu, Nan; Dong, Mei; Liu, Chunyan; Wang, Xiuli; Cong, Jianglin; Wang, Liqian; Wang, Xiaojie; Lakhani, Ishan; Liu, Xia; Hou, Jianqing; Wang, Shaoguang; Tse, Gary
Abstract: Endometrial cancer is a common gynecological malignancy in developed countries. Insulin has been identified as a risk factor for endometrial cancer. However, whether insulin levels are related to the risk of lymph node metastasis (LNM) in endometrial cancer is unknown. We conducted a prospective cohort study in a regional hospital to examine the relationships between insulin levels and risk of LNM in premenopausal and postmenopausal women. A total of 668 patients were recruited. Of these, 206 were premenopausal (mean age: 42.01 ± 10.17) and 462 were postmenopausal (mean age: 62.13 ± 13.85). The incidence of LNM in both premenopausal and postmenopausal groups was comparable at 7% and 8%, respectively. In premenopausal women, multivariate logistic regression demonstrated that insulin levels (OR: 2.11, 95% CI: 1.48–2.85, P  < 0.05) were significant predictors of LNM risk. In the same group, insulin levels remained significant predictors of LNM risk (cut‐off: 10.48  μ IU/mL) when adjusted for body mass index (BMI) (OR: 3.51, 95% CI: 1.42–5.98; P  < 0.05) or for waist‐to‐hip ratio (WHR) (OR: 1.87, 95% CI: 1.08–2.66; P  < 0.05). Similarly, in postmenopausal women, multivariate logistic regression showed that insulin levels (OR: 1.99, 95% CI: 1.30–2.89; P  < 0.05) also significantly predicted LNM risk. This relationship was maintained even after adjustment for BMI (cut‐off: 7.40  μ IU/mL, OR: 1.99, 95% CI: 1.01–3.12, P  < 0.05) or for WHR (cut‐off: 10.15  μ IU/mL, OR: 1.61, 95% CI: 1.04–2.35; P  < 0.05). Insulin levels are significantly associated with LNM risk in both premenopausal and postmenopausal women with endometrial cancer. Further prospective studies are needed to examine a potential causal relationship and determine whether its use can offer incremental value for risk stratification in this patient population. Abstract : Our novel findings are that (1) WHR, lesion diameter >2 cm, myometrial invasion ≥50%, pathological grade, and insulin levels were significant predictors of LNM risk in both premenopausal and postmenopausal women, (2) insulin level with a cut‐off of 10.48  μ IU/mL was predictive of LNM risk when adjusted for BMI (OR: 3.51, 1.42–5.98; P  < 0.05) or WHR (OR: 1.87, 1.08–2.66; P  < 0.05) in premenopausal women, and (3) insulin with a similar cut‐off of 10.15  μ IU/mL was predictive of LNM risk when adjusted for BMI (3.07, 1.26–5.40; P  < 0.05, respectively) or WHR (OR: 1.61, 1.04–2.35; P  < 0.05).